The Effect of Integrity, Task Complexity, and Work Motivation on The Performance of APIP (Government Internal Supervision Apparatus) Through Job Satisfaction as Intervening Variable - Ely Agustina; Gunistiyo; Dewi Indriasih (Permana : Jurnal Perpajakan, Manajemen, dan Akuntansi, 2022)
This study empirically examined the effect of integrity, task complexity and work motivation on APIP performance through job satisfaction (a case study at the Tegal Regency Inspectorate Office). The research variables in this study were integrity, task complexity and work motivation, APIP performance and job satisfaction. The hypothesis of thiThis research hypothesizes complexity and work motivation have a significant and positive effect on performance through job satisfaction. The data collection method used in this study was a questionnaire. While the data analysis method used is PLS. The results of this study are integrity has a significant positive effect on performance, task complexity has a positive effect on performance, motivation has no effect on performance, integrity has no effect on job satisfaction, work complexity has a positive effect on job satisfaction, motivation has a positive effect on job satisfaction, satisfaction has a positive effect on performance, patient satisfaction can mediate the influence of integrity and task complexity